Tumor Necrosis Factor α and Regulatory T Cells in Oncoimmunology - Salomon, Benoît L.; Leclerc, Mathieu; Tosello, Jimena; Ronin, Emilie; Piaggio, Eliane; Cohen, José L. (Frontiers in Immunology, 2018)
Tumor necrosis factor α (TNF) is a potent pro-inflammatory cytokine that has deleterious effect in some autoimmune diseases, which led to the use of anti-TNF drugs in some of these diseases. However, some rare patients treated with these drugs paradoxically develop an aggravation of their disease or new onset autoimmunity, revealing an immunosuppressive facet of TNF. A possible mechanism of this observation is the direct and positive effect of TNF on regulatory T cells (Tregs) through its binding to the TNF receptor type 2 (TNFR2). Indeed, TNF is able to increase expansion, stability and possibly function of Tregs via TNFR2. In this review, we discuss the role of TNF in graft-versus-host disease as an example of the ambivalence of this cytokine in the pathophysiology of an immuno-pathology, highlighting the therapeutic potential of triggering TNFR2 to boost Treg expansion. We also describe new targets in immunotherapy of cancer, emphasizing on the putative suppressive effect of TNF in anti-tumor immunity and of the interest of blocking TNFR2 to regulate the Treg compartment.